PENGEMBANGAN PARIWISATA MENGGUNAKAN MODEL PENTAHELIX DI KABUPATEN BELU - Carmo, Jemianus Yusuf A. V. Do; Kiak, Novi Theresia; Tiwu, Maria Indriyani Hewe (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2025)
In  an effort   to increase l tourism, the  government is  developing the   tourism sector l through the   pentahelix collaboration. Many tourism objects in Belu Regency have the potential  to be  developed because of their uniqueness. The Belu Regency Regional   Government seeks to  develop tourism l through collaboration with various l parties such l as the Belu Regency Tourism l Office, academics, media, business actors and   the community. However, it   is not  known to what extent the   involved parties are involved in   tourism development, thus, the  problem formulation l in this   research is how  the tourism development strategy uses the pentahelix model in Belu Regency. The aim l of this l research is l to explain and  formulate a tourism development strategy using the model. pentahelix in Belu Regency. The research  method used l was descriptive qualitative. The conclusion l in this   research is that  the pentahelix  model in  tourism development  in Belu Regency   has not   run optimally. This is l because collaboration   between actors  has not  yet taken place considering that there  is still  a tendency   for actors  to work  independently, apart from that there  is still l distrust between  actors. Keywords: Pentahelix, Development, Tourism Potential